Moral Economy - Asonzeh Ukah (Journal for the Study of Religion)
Since the re-purposing of the concept of the moral economy by the British historian, E.P. Thompson in the late 1960s, scholars from a variety of disciplines in social sciences and humanities have attempted to apply it as a tool for empirical analysis. As a migratory concept, the meaning of ‘moral economy’ has shifted from theology to philosophy to anthropology and history. Scholars of religions and historians of religion, however, have shown a reluctance in deploying the concept in their field of study. A flexible and vintage concept such as the moral economy may seem to be an oxymoron when applied to the study of religion and religious reforms. Its utility, however, is demonstrated by a collection of four critical articles in this special issue of this journal to explore wide-ranging empirical materials and contexts. These include the contemporary analysis of religious morality and regulation in Northern Nigeria, the entanglements of Muslim-owned restaurants and Islam-ic morality in Mumbai (India), Zulu ethnic nationality and morality in the Nazareth Baptist Church in KwaZulu-Natal (South Africa), and finally, the pre-modern theoretical and philosophical reflections of the 14th-century Tunisian Muslim philosopher, Abd al-Rahman Ibn Khaldun. In these diverse scenarios and contexts, the moral economy concept illustrates its theoretical and analytical capacity and potential in the field of the study of religions.